Measuring bacterial activity and community composition at high hydrostatic pressure using a novel experimental approach: a pilot study - Wannicke, Nicola; Frindte, Katharina; Gust, Giselher; Liskow, Iris; Wacker, Alexander; Meyer, Andreas; Grossart, Hans-Peter (FEMS microbiology ecology, 2015)
In this pilot study, we describe a high-pressure incubation system allowing multiple subsampling of a pressurized culture without decompression. The system was tested using one piezophilic (Photobacterium profundum), one piezotolerant (Colwellia maris) bacterial strain and a decompressed sample from the Mediterranean deep sea (3044 m) determining bacterial community composition, protein production (BPP) and cell multiplication rates (BCM) up to 27 MPa. The results showed elevation of BPP at high pressure was by a factor of 1.5 ± 1.4 and 3.9 ± 2.3 for P. profundum and C. maris, respectively, compared to ambient-pressure treatments and by a factor of 6.9 ± 3.8 fold in the field samples. In P. profundum and C. maris, BCM at high pressure was elevated (3.1 ± 1.5 and 2.9 ± 1.7 fold, respectively) compared to the ambient-pressure treatments. After 3 days of incubation at 27 MPa, the natural bacterial deep-sea community was dominated by one phylum of the genus Exiguobacterium, indicating the rapid selection of piezotolerant bacteria. In future studies, our novel incubation system could be part of an isopiestic pressure chain, allowing more accurate measurement of bacterial activity rates which is important both for modeling and for predicting the efficiency of the oceanic carbon pump. Consistently higher bacterial activities when measured at high pressure (27 MPa) along with changes in community composition.